L-Methioninase as a Selective Anticancer Agent: Dose-Dependent Cytotoxicity and Metastasis Suppression in Methionine-Dependent Tumor Cells - Abbas Abed Noor Al-Owaidi; Mohammed Abdullah Jebor (Acta Medica Iranica)
L-methioninase (L-Met), a methionine-degrading enzyme, has shown potential for anticancer therapy. Many tumor tissues have a limited ability to produce methionine and depend on external sources; hence, these tumors can be targeted by methionine-based treatments. The present study was conducted to investigate the effects of L-Met on cancer cells, particularly hepatocellular carcinoma (HepG2) and pancreatic carcinoma (PANC-1), and to evaluate its viability as a therapeutic agent. Various techniques, including ammonium sulfate precipitation, dialysis, ion-exchange chromatography, and gel filtration chromatography, were employed to purify the enzyme L-Met. A cytotoxicity test was conducted against HepG2 and PANC-1 cells (at 25-200 µg/mL concentrations), using the MTT to evaluate cell viability, total nuclear intensity (TNI), and cell membrane permeability (CMP). Statistical analysis was done using one-way ANOVA and Dunnett's multiple comparisons test to compare study groups. L-Met displayed dose-dependent growth inhibition of the specified cell lines. The PANC-1 cell line exhibited an IC50 of 64.68 µg/mL, indicating a higher sensitivity to L-Met compared to WRL 68 normal cells, which had an IC50 of 214.0 µg/mL. Regarding HepG2, an even lower IC₅₀ of 66.44 µg/mL was observed, further confirming the selective targeting of cancer cells by L-Met. Treatment with L-Met at a 200 µg/mL concentration significantly decreased TNI and CMP levels in both the PANC-1 and HepG2 cell lines, indicating increased cytotoxicity and compromised membrane integrity. Additionally, L-Met reduced matrix metalloproteinase activities in both cancer cell lines, a critical factor in metastasis. Our study demonstrates the dose-dependent cytotoxic effects of L-Met on methionine-dependent tumor cells, specifically HepG2 and PANC-1. These findings highlight the need for optimized L-Met dosing strategies in cancer treatment, particularly for methionine-dependent malignancies, paving the way for its potential use in targeted cancer therapy.